2010
DOI: 10.1128/iai.00374-10
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Proteomic Analysis of Extracellular Proteins of Clostridium perfringens Type A and Type C Strains

Abstract: Clostridium perfringens is a medically important clostridial pathogen and an etiological agent causing several diseases in humans and animals. C. perfringens and its toxins have been listed as potential biological and toxin warfare (BTW) agents; thus, efforts to develop strategies for detection and protection are warranted. Fortyeight extracellular proteins of C. perfringens type A and type C strains have been identified here using a 2-dimensional gel electrophoresis-mass spectrometry (2-DE-MS) technique. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 53 publications
1
51
0
Order By: Relevance
“…The C. perfringens SagA protein has a signal sequence compatible for secretion via the Sec pathway (not shown). The SagA homolog in C. perfringens strain ATCC 13124 was identified as the most abundant secreted protein, even more so than alpha toxin and collagenase, two wellstudied secreted toxins (24). This is consistent with our observation that even maximum expression from the P bgaL promoter on a multicopy plasmid did not fully complement the sagA mutants.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The C. perfringens SagA protein has a signal sequence compatible for secretion via the Sec pathway (not shown). The SagA homolog in C. perfringens strain ATCC 13124 was identified as the most abundant secreted protein, even more so than alpha toxin and collagenase, two wellstudied secreted toxins (24). This is consistent with our observation that even maximum expression from the P bgaL promoter on a multicopy plasmid did not fully complement the sagA mutants.…”
Section: Discussionsupporting
confidence: 89%
“…This is consistent with our observation that even maximum expression from the P bgaL promoter on a multicopy plasmid did not fully complement the sagA mutants. The C. perfringens SagA protein displayed three different isoforms in two-dimensional gel electrophoresis, which suggests posttranslational modification of the protein (24).…”
Section: Discussionmentioning
confidence: 99%
“…M. tuberculosis MprB and its orthologs all possessed two transmembrane domains flanking a relatively large ECD of ϳ100 amino acids, a cytoplasmic HAMP (present in histidine kinases, adenylate cyclases, methyl-accepting proteins, and phosphatases) domain, and sensor kinase DHp (dimerization and histidine phosphotransfer) and CA (catalytic and ATP-binding) domains (data not shown). The DHp domain is necessary for SK function, since it contains residues conferring SK-RR specificity (43)(44)(45)(46)(47)(48), SK dimerization and autophosphorylation activity (49)(50)(51), and kinase and phosphatase activity (52). We rationalized that the DHp domain of MprB orthologs may therefore be the most conserved.…”
Section: Resultsmentioning
confidence: 99%
“…While DnaK was originally thought to be exclusively cytoplasmic, several studies have now reported the localization of DnaK outside the cell, including in Mycobacterium spp. (67)(68)(69)(70) and other Gram-positive bacteria (51,(71)(72)(73)(74). DnaK is a member of the well-conserved Hsp70 family of proteins found in all kingdoms of life.…”
Section: Discussionmentioning
confidence: 99%
“…Active immunization using inactive toxin moiety was demonstrated to yield positive results in animal model [7,8]. Importance of non-toxin protein antigens in disease expression, especially in colonization by the pathogenic bacteria, including Clostridium difficile, has been recently recognized [9,10]. Preparedness for bioterrorism or state sponsored warfare using biological agents requires development of effective pre-exposure prophylactic regimen as post-exposure therapies are plagued with antibiotic resistant strains.…”
Section: Introductionmentioning
confidence: 99%